Membrane-electrode assembly of fuel cell having improved mechanical strength and proton conductivity and method for manufacturing the same

By combining phosphonic acid functionalized graphene oxide with perfluorosulfonic acid ionomer to form an electrolyte membrane, the problem of insufficient mechanical stability and proton conductivity of perfluorosulfonic acid ionomer electrolyte membrane at high temperature is solved, and the problem of insufficient mechanical stability and proton conductivity of perfluorosulfonic acid ionomer electrolyte membrane at high temperature is achieved. The high water absorption rate and proton conductivity are improved, ensuring the stable operation of fuel cells at high temperatures and efficient performance under high humidity.

CN111628200BActive Publication Date: 2025-01-14HYUNDAI MOTOR CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201911128101.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-02-27
Filing Date
2019-11-18
Publication Date
2025-01-14
Estimated Expiration
2039-11-18

AI Technical Summary

Technical Problem

The existing perfluorosulfonic acid ionomer electrolyte membranes have insufficient mechanical stability and proton conductivity at high temperatures, which limits the operating temperature of the fuel cell and is difficult to maintain the optimal moisture state.

Method used

The phosphonic acid-functionalized graphene oxide is used to combine with perfluorosulfonic acid ionomer to form an electrolyte membrane. The water absorption and proton conductivity of the membrane are increased through the covalent bonding of phosphonic acid and graphene oxide, and the membrane is enhanced through the porous reinforcement of the membrane. Mechanical stability of the support membrane.

Benefits of technology

The water absorption and proton conductivity of the electrolyte membrane are improved, mechanical stability and dimensional stability are enhanced, so that the fuel cell can operate at temperatures above 95°C and maintain high proton conductivity under different humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111628200B_ABST
    Figure CN111628200B_ABST
Patent Text Reader

Abstract

The present invention discloses a membrane-electrode assembly for a fuel cell with improved mechanical strength and proton conductivity and a method for manufacturing the same. The membrane-electrode assembly for a fuel cell may include an electrolyte membrane, the electrolyte membrane comprising phosphonic acid-functionalized graphene oxide to improve its mechanical strength and proton conductivity, and a method for manufacturing the membrane-electrode assembly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a membrane-electrode assembly of a fuel cell and a method for manufacturing the same. In particular, the membrane-electrode assembly of the fuel cell may include an electrolyte membrane, wherein the electrolyte membrane contains graphene oxide functionalized with phosphonic acid to improve its mechanical strength and proton conductivity. Background Art

[0002] Electrolyte membranes containing perfluorosulfonic acid ionomers have been most widely used in the field of polymer electrolyte membrane fuel cells because the electrolyte membranes exhibit high proton conductivity and high stability at high humidity. However, since electrolyte membranes based on pure perfluorosulfonic acid ionomers have low glass transition temperatures and low proton conductivity at high temperatures, the mechanical stability and dimensional stability of the electrolyte membranes may be greatly reduced. For these reasons, fuel cells applying ordinary perfluoroionomer electrolyte membranes can only operate at a restricted temperature of 95°C or below. In addition, since the proton conductivity of perfluoroionomer-based electrolyte membranes mainly depends on the proton conduction mechanism through sulfonic acid at the location where water exists, it is very important to keep the electrolyte membrane in an optimal moisture state.

[0003] In recent years, attempts have been made to mix perfluorosulfonic acid ionomer-based electrolytes with graphene oxide to improve the proton conductivity and thermal and mechanical properties of the electrolyte membrane. In this case, due to the unique flat structure and wide surface area of ​​graphene oxide, a large number of proton transfer channels can be provided and a large amount of water can be retained. In addition, the mechanical properties of the electrolyte membrane can be improved.

[0004] The above information disclosed in the background technology section is only intended to deepen the understanding of the background technology of the present invention, and therefore the information contained therein does not constitute the prior art that is already known to those skilled in the art in this country. Summary of the invention

[0005] In a preferred aspect, a membrane-electrode assembly is provided, the membrane-electrode assembly comprising an electrolyte membrane having improved water absorption properties. The membrane-electrode assembly comprising the electrolyte membrane can have a high proton conductivity. A membrane-electrode assembly comprising an electrolyte membrane is also provided, the electrolyte membrane exhibiting a higher proton conductivity than a perfluorosulfonic acid (nafion) electrolyte membrane.

[0006] A membrane-electrode assembly is also provided, which includes an electrolyte membrane having improved mechanical stability and dimensional stability.

[0007] The object of the present invention is not limited to the above-mentioned object. The object of the present invention will be clearly understood through the following description, and can be achieved by the means defined in the claims and their combination.

[0008] In one aspect, a membrane-electrode assembly for a fuel cell is provided. The membrane-electrode assembly may include an electrolyte membrane and a pair of electrodes disposed on a first surface and a second surface of the electrolyte membrane including graphene oxide. The graphene oxide may include phosphonic acid (PO 3 H 2 ), so graphene oxide can be functionalized with phosphonic acid.

[0009] The first surface and the second surface of the electrolyte membrane face each other in opposite directions.

[0010] The term "functionalized graphene oxide" as used herein refers to graphene oxide containing functional groups (e.g., chemical functional groups) in or on the surface. Preferably, the functionalized graphene oxide can be functionalized by attaching to chemical functional groups, such as forming covalent bonds through its oxygen-containing functional groups (e.g., carboxyl, hydroxyl, epoxy). In certain embodiments, graphene oxide can be functionalized by attaching phosphonic acid to its surface, and covalent bonds can be formed between the carboxyl, hydroxyl, or epoxy groups of the graphene oxide and the phosphonic acid.

[0011] The electrolyte membrane may suitably comprise a perfluorosulfonic acid ionomer (PFSA).

[0012] The electrolyte membrane may include the phosphonic acid functionalized graphene oxide in an amount of about 0.01 wt % to 10.0 wt % based on the total weight of the electrolyte membrane.

[0013] The electrolyte membrane may have a water absorption rate of about 50% or more.

[0014] The electrolyte membrane may have a proton conductivity of about 0.04 to 0.40 S / cm.

[0015] The graphene oxide may suitably contain one or more oxygen-containing functional groups selected from the group consisting of a carboxyl group, a hydroxyl group, an epoxy group, and combinations thereof. Preferably, the phosphonic acid may form a covalent bond with the oxygen of the oxygen-containing functional group.

[0016] The membrane-electrode assembly may further include a pair of ionomer composite membranes, each of which may include a porous reinforcement membrane. The ionomer composite membrane may be appropriately disposed between the electrode and the electrolyte membrane so as to be attached to opposite surfaces of the electrolyte membrane.

[0017] Each ionomer composite membrane may further include a perfluorosulfonic acid ionomer, and the ionomer may be impregnated into the pores of the porous reinforced membrane.

[0018] The porous reinforced membrane may appropriately include one or more selected from polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (e-PTFE), polyethylene (PE), polypropylene (PP), polyphenylene ether (PPO), polybenzimidazole (PBI), polyimide (PI), polyvinylidene fluoride (PVdF) and polyvinyl chloride (PVC).

[0019] In another aspect, the present invention provides a method for manufacturing a membrane-electrode assembly for a fuel cell. The method may include: preparing a first mixture comprising a phosphonic acid precursor material and graphene oxide; preparing a second mixture comprising an active additive and the first mixture; separating the second mixture into a liquid phase and a solid phase; drying the separated solid material to obtain a solid powder; washing the solid powder to obtain a phosphonic acid functionalized graphene oxide (PGO); preparing a third mixture comprising a phosphonic acid functionalized graphene oxide and a perfluorosulfonic acid ionomer solution; preparing an electrolyte membrane by coating and drying the third mixture and attaching electrodes to the first and second surfaces of the electrolyte membrane.

[0020] The phosphonic acid precursor material may suitably include triethyl phosphite (P(OEt) 3 ).

[0021] Preferably, when preparing the first mixture, graphene oxide in an amount of about 0.1 to 1.0 parts by weight may be mixed with 100 parts by weight of the phosphonic acid precursor material.

[0022] The active additive may include lithium bromide (LiBr).

[0023] Preferably, in preparing the second mixture, the active additive may be introduced into the first mixture in an amount of about 0.2 to 2.0 parts by weight based on 100 parts by weight of the phosphonic acid precursor material.

[0024] The solid powder may be washed with one or more selected from tetrahydrofuran, dimethylformamide and water to obtain phosphonic acid functionalized graphene oxide.

[0025] The electrolyte membrane may suitably include the phosphonic acid functionalized graphene oxide in an amount of about 0.01 wt % to 10.0 wt % based on the total weight of the electrolyte membrane.

[0026] Prior to attaching the electrodes, the method may further include attaching an ionomer composite membrane to the first and second surfaces of the electrolyte membrane. Preferably, each ionomer composite membrane may include a porous reinforced membrane, and pores of the porous reinforced membrane may be impregnated with the perfluorosulfonic acid ionomer.

[0027] Other aspects and preferred embodiments of the invention are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and other features of the present invention will now be described in detail with reference to certain exemplary embodiments shown in the accompanying drawings, which are herein used for illustrative purposes only and are therefore non-limiting to the present invention, wherein:

[0029] Figure 1 shows an exemplary electrolyte membrane according to an exemplary embodiment of the present invention;

[0030] Figure 2 shows an exemplary embodiment in which an ionomer composite membrane is applied to an exemplary electrolyte membrane of the present invention;

[0031] Figure 3 An exemplary method of manufacturing an exemplary membrane-electrode assembly according to an exemplary embodiment of the present invention is shown;

[0032] Figure 4 Exemplary electrolyte membranes according to examples and comparative examples of the present invention are shown;

[0033] Figure 5 is a graph showing water absorption properties of exemplary electrolyte membranes according to examples of the present invention and comparative examples;

[0034] Figure 6 is a graph showing changes in proton conductivity of exemplary electrolyte membranes according to examples of the present invention and comparative examples as a function of temperature; and

[0035] Figure 7 is a graph showing changes in proton conductivity of exemplary electrolyte membranes according to examples of the present invention and comparative examples as a function of relative humidity.

[0036] It should be understood that the accompanying drawings are not necessarily to scale, and show slightly simplified representations of various preferred features that illustrate the basic principles of the invention. The specific design features of the present invention disclosed herein (including, for example, specific dimensions, orientations, locations, and shapes) will be determined in part by the specific intended application and use environment.

[0037] In the figures, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures of the drawing. DETAILED DESCRIPTION

[0038] The above objects and other objects, features and advantages will be clearly understood through the following preferred embodiments and with reference to the accompanying drawings. However, the present invention is not limited to the embodiments but is embodied in different forms. The proposed embodiments are only intended to provide a thorough and complete understanding of the disclosed content and are sufficient to inform those skilled in the art of the technical concept of the present invention.

[0039] Throughout the description of the accompanying drawings, the same reference numerals represent the same elements. In the accompanying drawings, for clarity, the size of the structure is exaggerated. It will be understood that although the terms "first", "second", etc. may be used herein to describe various elements, these elements should be understood to be not limited by these terms, which are only used to distinguish one element from another element. For example, within the scope defined by the present invention, the first element may be referred to as the second element and similarly, the second element may be referred to as the first element. Unless the context clearly indicates otherwise, the singular form is intended to include the plural form.

[0040] It will also be understood that when the terms "comprising", "having", etc. are used in the specification, it means that the features, values, steps, operations, elements, components or combinations thereof are present, but the presence or addition of one or more other features, values, steps, operations, elements, components or combinations thereof is not excluded. It will also be understood that when an element such as a layer, film, region or substrate is referred to as being "on another element", it can be directly on the other element or there can be intervening elements. It will also be understood that when an element such as a layer, film, region or substrate is referred to as being "under another element", it can be directly under the other element or there can be intervening elements.

[0041] Unless the context clearly indicates otherwise, all numerical values, numbers and / or expressions of representative ingredients, reaction conditions, polymer compositions and mixture amounts used in the specification are approximate values, reflecting the various measurement uncertainties inherent in obtaining these numbers. For this reason, it should be understood that in all cases, the term "about" should modify all numerical values, numbers and / or expressions. Unless otherwise stated or obvious from the context, the term "about" used herein is understood to be within the normal tolerance range of this field, such as within 2 average standard deviations. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the specified value. Unless it is clear from the context, all numerical values ​​provided herein are modified by the term "about".

[0042] In addition, when numerical ranges are disclosed in the specification, unless otherwise defined, these ranges are continuous and include all values ​​from the minimum value to the maximum value, including the maximum value in the range. In addition, when ranges involve integers, unless otherwise defined, they include all integers from the minimum value to the maximum value, including the maximum value in the range.

[0043] It should be understood that in the specification, when a range refers to a parameter, the parameter covers all numbers disclosed in the range, including endpoints. For example, the range of "5 to 10" includes the numbers of 5, 6, 7, 8, 9 and 10, and any subranges, such as the ranges of 6 to 10, 7 to 10, 6 to 9 and 7 to 9, and any numbers, such as 5.5, 6.5, 7.5, 5.5 to 8.5 and 6.5 to 9, falling between the appropriate integers in the range. In addition, for example, the range of "10% to 30%" includes all integers, including numbers such as 10%, 11%, 12% and 13% and 30%, and any subranges of 10% to 15%, 12% to 18% or 20% to 30%, and any numbers falling between the appropriate integers in the range, such as 10.5%, 15.5% and 25.5%.

[0044] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0045] It should be understood that the term "vehicle" or "vehicular" or other similar terms used herein generally include motor vehicles, such as passenger automobiles including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, ships including various boats, marine vessels, aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles, and other alternative fuel vehicles (e.g., fuels derived from non-petroleum energy sources). As mentioned herein, a hybrid vehicle is a vehicle having two or more power sources, such as a gasoline-powered vehicle and an electric-powered vehicle.

[0046] The present invention relates to a membrane-electrode assembly for a fuel cell and a method for manufacturing the same. In particular, the membrane-electrode assembly for a fuel cell may include an electrolyte membrane, wherein the electrolyte membrane contains graphene oxide functionalized with phosphonic acid, thereby improving its mechanical strength and proton conductivity.

[0047] Hereinafter, a membrane-electrode assembly and a method for manufacturing the same will be described respectively.

[0048] Membrane-electrode assembly

[0049] The membrane-electrode assembly according to an exemplary embodiment of the present invention includes: an electrolyte membrane and a pair of electrodes disposed on opposite surfaces (a first surface and a second surface) of the electrolyte membrane. The electrolyte membrane may include graphene oxide, and phosphonic acid (PO 3 H 2 ) can be functionalized in graphene oxide. Graphene oxide can be functionalized, for example, by attaching phosphonic acid to add functional groups, such as chemical functional groups.

[0050] Figure 1 An exemplary electrolyte membrane according to an exemplary embodiment of the present invention is shown. Figure 1 As shown, the electrolyte membrane A may include perfluorosulfonic acid ionomer (PFSA) 10. In particular, the electrolyte membrane may include phosphonic acid functionalized graphene oxide 20 and perfluorosulfonic acid ionomer 10.

[0051] The phosphonic acid-functionalized graphene oxide 20 may be dispersed in the perfluorosulfonic acid ionomer 10. As a result, the water absorption and proton conductivity of the electrolyte membrane A may be improved.

[0052] In the phosphonic acid functionalized graphene oxide, the graphene oxide may include oxygen-containing functional groups, such as carboxyl, hydroxyl, epoxy, and combinations thereof. The phosphonic acid may be functionalized or attached due to covalent bonding with the oxygen of the oxygen-containing functional group.

[0053] Graphene is a material in which carbon is bonded in a two-dimensional honeycomb structure and has a basic form of a carbon-carbon bonded material, while graphene oxide has a form in which a functional group such as a carboxyl group, a hydroxyl group, or an epoxy group is bonded to the basic form.

[0054] Since the phosphonic acid is directly covalently bonded to the oxygen-containing functional groups of graphene oxide, the number of phosphonic acid functional groups per unit size of graphene oxide domain can be increased compared to the case where the phosphonic acid is functionalized to graphene oxide using a hydrocarbon chain with a large volume. Therefore, the surface roughness of the graphene oxide functionalized with phosphonic acid according to an exemplary embodiment of the present invention can be increased, and its hydrophilic domain can be expanded, thereby increasing the proton conductivity of the electrolyte membrane. In addition, the phosphonic acid can be directly attached to the graphene oxide by covalent bonding, and excessive swelling of the electrolyte membrane can be prevented.

[0055] Since phosphonic acid is a very strong acid, its corrosiveness can be very high. When phosphonic acid is directly mixed with perfluorosulfonic acid ionomer, the phosphonic acid can leach out during fuel cell operation. However, when the phosphonic acid is covalently bonded to graphene oxide and then mixed with perfluorosulfonic acid ionomer, no leaching occurs.

[0056] The electrolyte membrane may include phosphonic acid functionalized graphene oxide in an amount of about 0.01 wt % to 10.0 wt %, about 0.1 wt % to 5.0 wt %, or particularly about 0.5 wt % to 2.0 wt %, based on the total weight of the electrolyte membrane. When the content of phosphonic acid functionalized graphene oxide is less than about 0.01 wt %, sufficient effect can be obtained by applying phosphonic acid functionalized graphene oxide. When the content of phosphonic acid functionalized graphene oxide is greater than about 10.0 wt %, the content of phosphonic acid functionalized graphene oxide may be excessive, and thus the brittleness of the electrolyte membrane may increase and the mechanical strength of the electrolyte membrane may decrease.

[0057] The electrodes are attached to opposite surfaces of the electrolyte membrane. In other words, the electrodes are attached to the first surface and the second surface of the electrolyte membrane, and the first surface faces the second surface in opposite directions. In particular, the fuel electrode (anode) that reacts with external hydrogen and the air electrode (cathode) that reacts with external oxygen are attached to opposite surfaces of the electrolyte membrane.

[0058] On the fuel electrode, external hydrogen can be separated into protons (hydrogen cations) and electrons, the separated hydrogen cations move to the air electrode through the electrolyte membrane in contact with the fuel electrode, and the electrons move to the air electrode via the wire connected to the fuel cell. In particular, each of the fuel electrode and the air electrode contains catalyst particles, and the catalyst particles react with external oxygen and hydrogen and serve as a path for electrons to move.

[0059] The electrode according to various exemplary embodiments of the present invention is not particularly limited as long as the electrode reacts with external gas to move electrons in the conventional fuel cell field. Generally, the electrode includes carbon in which platinum particles are dispersed.

[0060] The membrane-electrode assembly according to an exemplary embodiment of the present invention may further include an ionomer composite membrane. In particular, the ionomer composite membrane may be disposed between the electrode and the electrolyte membrane such that the electrode and the electrolyte membrane are attached to opposite surfaces of each ionomer composite membrane.

[0061] Figure 2 Exemplary electrolyte membranes and ionomer composite membranes are shown. Figure 2 As shown, the ionomer composite membranes B may be disposed on opposite surfaces of the electrolyte membrane A. Each ionomer composite membrane B may include a porous reinforced membrane 30 and a perfluorosulfonic acid ionomer 10 , and the ionomer may be impregnated into pores of the porous reinforced membrane 30 .

[0062] The ionomer composite membrane according to the present invention can improve the proton conductivity of the electrolyte membrane, and can be attached to the opposite surface of the electrolyte membrane to support the electrolyte membrane.

[0063] Since the fuel cell operates at a temperature higher than about 50°C, dehydration may occur repeatedly due to its electrochemical reaction, and thus wrinkling deformation may occur due to repeated shrinkage and swelling of the electrolyte membrane. At this time, the ionomer composite membrane may be fixed to the opposite surface of the electrolyte membrane, which repeatedly shrinks and swells to appropriately disperse the stress generated by the local shrinkage and swelling of the electrolyte membrane, thereby preventing deformation of the electrolyte membrane to the greatest extent.

[0064] Method for manufacturing membrane-electrode assembly

[0065] According to an exemplary embodiment of the present invention, a method for manufacturing a membrane-electrode assembly may include: a step of mixing a phosphonic acid precursor material and graphene oxide to prepare a first mixture; a step of introducing and dispersing an active additive into the first mixture to prepare a second mixture; a step of separating the second mixture into a liquid phase and a solid phase; a step of drying the separated solid material to obtain a solid powder; a step of washing the solid powder to obtain phosphonic acid functionalized graphene oxide (PGO); a step of mixing the phosphonic acid functionalized graphene oxide with a perfluorosulfonic acid ionomer solution to prepare a third mixture; a step of coating and drying the third mixture to manufacture an electrolyte membrane; and a step of attaching electrodes to opposite surfaces of the electrolyte membrane.

[0066] Figure 3 FIG. 2 is a flow chart showing an exemplary method for manufacturing an exemplary membrane-electrode assembly according to the present invention. Figure 3 As shown, each step will be described in more detail.

[0067] First mixture preparation step

[0068] The first mixture can be prepared by mixing a phosphonic acid precursor material and graphene oxide. The phosphonic acid precursor material used herein can provide a phosphonic acid functionalized to graphene oxide. In particular, the phosphonic acid precursor material can include triethyl phosphite (P(OEt) 3 ). Preferably, the graphene oxide in an amount of about 0.1 to 1.0 parts by weight, particularly about 0.1 to 0.5 parts by weight, can be mixed with 100 parts by weight of triethyl phosphite. When the content of graphene oxide is less than about 0.1 parts by weight, the percentage of phosphonic acid functionalized to graphene oxide may decrease, and thus it is difficult to obtain a sufficient phosphonic acid functionalization effect. When the content of graphene oxide is greater than about 10 parts by weight, the reaction efficiency may decrease.

[0069] Since triethyl phosphite forms a hydrocarbon chain with a small volume, triethyl phosphite can be functionalized to the domains of graphene oxide with high density.

[0070] Second mixture preparation step

[0071] The second mixture can be prepared by introducing and dispersing the active additive into the first mixture. The active additive can be added to activate the oxygen groups present on the surface of the graphene oxide. After activation is completed, the oxygen groups can easily bond to the phosphonic acid precursor material.

[0072] Preferably, the active additive may include lithium bromide (LiBr).

[0073] For example, based on 100 parts by weight of the phosphonic acid precursor material, an amount of about 0.2 to 2.0 parts by weight, an amount of about 0.2 to 1.0 parts by weight, and / or particularly an amount of about 0.2 to 0.5 parts by weight of the active additive may be introduced into the first mixture. When the content of the active additive is less than about 0.2 parts by weight, it may be difficult to perfectly activate the oxygen groups of graphene oxide. When the content of the active additive is greater than about 2.0 parts by weight, the activation efficiency may be reduced.

[0074] In order to uniformly mix the active additive with the first mixture, a separate dispersion may be performed. The dispersion may be ultrasonic dispersion (ultrasonic treatment), and may be appropriately performed for about 10 to 120 minutes.

[0075] Separation steps

[0076] The second mixture can be separated into a liquid phase and a solid phase, for example, by stirring, centrifuging, and filtering the second mixture, thereby separating the second mixture into a liquid phase and a solid phase. Performing a typical separation operation is sufficient to separate the second mixture into a liquid phase and a solid phase. For example, the separation operation can be suitably carried out under nitrogen (N 2 ) atmosphere at a temperature of about 80 to 120° C. for about 10 to 50 hours, thereby obtaining better results. At this time, the centrifugal separation may be performed at about 3000 to 5000 rpm.

[0077] Solid powder obtaining steps

[0078] The solid powder may be obtained by separating the solid phase t in the separation step. Preferably, the drying may be performed at a temperature of 60 to 90° C. for about 6 to 24 hours.

[0079] Preparation steps of phosphonic acid functionalized graphene oxide

[0080] Phosphonic acid functionalized graphene oxide can be obtained by washing the dried solid powder. For example, the solid powder can be washed with one or more selected from tetrahydrofuran, dimethylformamide and water, preferably once or more times, to obtain phosphonic acid functionalized graphene oxide. At this time, a final wash can be performed with water. For example, the ethoxy group of triethyl phosphite can be converted to a hydroxyl group by washing with water, and phosphonic acid functionalized graphene oxide can be obtained.

[0081] Third mixture preparation step

[0082] A third mixture may be prepared by mixing the phosphonic acid functionalized graphene oxide with the perfluorosulfonic acid ionomer solution.

[0083] Preferably, the dried electrolyte membrane may contain phosphonic acid functionalized graphene oxide in an amount of about 0.01 to 10.0 wt %, or particularly about 0.1 to 5.0 wt %, based on the total weight of the electrolyte membrane. When the content of phosphonic acid functionalized graphene oxide is less than about 0.01 wt %, the water absorption and proton conductivity of the electrolyte membrane may be reduced. When the content of phosphonic acid functionalized graphene oxide is greater than about 10.0 wt %, the brittleness of the electrolyte membrane increases, and thus the mechanical strength of the electrolyte membrane decreases.

[0084] Electrolyte membrane manufacturing steps

[0085] The electrolyte membrane can be manufactured by, for example, coating the third mixture on a substrate and drying the third mixture. The coating and drying methods are not particularly limited. It is sufficient to use coating and drying methods commonly used in the field of fuel cells.

[0086] Electrode Attachment Steps

[0087] The fuel electrode (eg, cathode or anode) and the oxygen electrode may be attached to the opposing surfaces (first and second surfaces) of the manufactured electrolyte membrane. The attachment step is not particularly limited as long as the attachment step is generally used in the field of fuel cells to manufacture a membrane-electrode assembly.

[0088] Ionomer composite membrane attachment steps

[0089] The ionomer composite membrane may be applied to the electrolyte membrane to improve the durability of the electrolyte membrane as desired. The ionomer composite membrane may preferably be applied to the electrolyte membrane prior to the electrode attachment step. For example, the ionomer composite membrane may be disposed between the electrode and the electrolyte membrane to be attached to the opposing surface of the electrolyte membrane.

[0090] Each ionomer composite membrane according to the present invention may include a porous reinforced membrane and a perfluorosulfonic acid ionomer. For example, the ionomer may be impregnated into the pores of the porous reinforced membrane. The impregnation method is not particularly limited as long as the pores of the porous reinforced membrane can be fully impregnated with the perfluorosulfonic acid ionomer using the impregnation method.

[0091] Example

[0092] Below, the present invention will be described in more detail with reference to specific examples. However, the following examples are only for the purpose of helping to understand the description of the present invention, and the present invention is not limited to the following examples.

[0093] Manufacturing Example

[0094] 300ml of triethyl phosphite (25°C, 0.969g / ml) was introduced into a round flask, 300mg of graphene oxide was added, and stirring was performed for about 2 hours. Subsequently, 800mg of lithium bromide (LiBr) was added to the graphene oxide dispersion solution, and ultrasonic dispersion was further performed for about 60 minutes. The mixed solution was stirred for 48 hours at a temperature of 100°C in a nitrogen atmosphere, and centrifuged at 4000rpm to separate the solution into a liquid phase and a solid phase. Subsequently, the solid powder filtrate was dried at a temperature of 75°C for about 12 hours. The final dried powder was washed with tetrahydrofuran and dimethylformamide mixed in a 1:1 ratio, and then washed with water to obtain phosphonic acid functionalized graphene oxide.

[0095] Example 1

[0096] The phosphonic acid functionalized graphene oxide (PGO) obtained according to the Manufacturing Example was mixed with a perfluorosulfonic acid ionomer so that the content of the phosphonic acid functionalized graphene oxide became 0.5 wt %, and the well-mixed solution was applied to a substrate to manufacture an electrolyte membrane.

[0097] Examples 2 to 4

[0098] Phosphonic acid-functionalized graphene oxide was added to have the content shown in Table 1, and the electrolyte membranes according to Examples 2 to 4 were manufactured using the same method as Example 1.

[0099] [Table 1]

[0100] Example 1 Example 2 Example 3 Example 4 PGO 0.5 wt% 1.0 wt% 1.5 wt% 2.0 wt%

[0101] Comparative Example 1

[0102] The electrolyte membrane was fabricated using the same method as in Example 1, using 100% perfluorosulfonic acid ionomer without the addition of phosphonic acid functionalized graphene oxide.

[0103] Experimental example

[0104] Figure 4 is a diagram showing exemplary electrolyte membranes manufactured according to Examples 1 to 4 and Comparative Example 1. Figure 4 The electrolyte membrane (a1) according to Comparative Example 1, the electrolyte membrane (a2) according to Example 1, the electrolyte membrane (a3) ​​according to Example 2, the electrolyte membrane (a4) according to Example 3 and the electrolyte membrane (a5) according to Example 4 are shown, and it can be seen that as the content of phosphonic acid-functionalized graphene oxide increases, the color of the electrolyte membrane becomes darker.

[0105] The water absorption property, the change of proton conductivity with temperature, and the change of proton conductivity with relative humidity of the electrolyte membrane were examined, and the results are as follows.

[0106] Experimental Example 1 (Water Absorption Properties)

[0107] Figure 5 is a graph showing the water absorption properties of the electrolyte membranes according to Examples 1 to 4 and Comparative Example 1.

[0108] In the case of Comparative Example 1, it can be seen that the water absorption property value of the electrolyte membrane manufactured using pure perfluorosulfonic acid ionomer without adding PGO is about 41%. In the case of Examples 1 to 4, it can be seen that the water absorption rate of each electrolyte membrane to which PGO is added increases. In particular, the water absorption rate of the electrolyte membrane according to Example 1 is 55%, the water absorption rate of the electrolyte membrane according to Example 2 is 60%, the water absorption rate of the electrolyte membrane according to Example 3 is 57%, and the water absorption rate of the electrolyte membrane according to Example 4 is 54%.

[0109] Experimental Example 2 (Proton conductivity changes with temperature)

[0110] Figure 6 is a graph showing changes in proton conductivity of the electrolyte membranes according to Examples 1 to 4 and Comparative Example 1 depending on temperature.

[0111] The proton conductivity test was conducted at a temperature between 40 and 90°C and a relative humidity of 100%.

[0112] Each of the electrolyte membranes according to Examples 1 to 4 exhibits high proton conductivity within the temperature range, compared to Comparative Example 1. In particular, it can be seen that the electrolyte membrane according to Example 2 has the highest conductivity value.

[0113] Experimental Example 3 (Proton conductivity changes with relative humidity)

[0114] Figure 7 is a graph showing changes in the proton conductivity of the electrolyte membranes according to Comparative Example 1 and Example 2 depending on the relative humidity.

[0115] The electrolyte membrane according to Example 2 exhibits high proton conductivity over the entire relative humidity range. In particular, it can be seen that the proton conductivity of the electrolyte membrane according to Example 2 at low humidity (40%) is greater than the proton conductivity of the electrolyte membrane according to Comparative Example 1 at 90% relative humidity, and the difference in proton conductivity between the electrolyte membrane according to Example 2 and the electrolyte membrane according to Comparative Example 1 further increases with increasing relative humidity.

[0116] Preferably, a membrane-electrode assembly is provided, comprising an electrolyte membrane having improved water absorption properties. In addition, a membrane-electrode assembly can be provided, comprising an electrolyte membrane having high proton conductivity. A membrane-electrode assembly is also provided, comprising an electrolyte membrane having higher proton conductivity than a perfluorosulfonic acid (nafion) electrolyte membrane. A membrane-electrode assembly is also provided, comprising an electrolyte membrane having improved mechanical stability and dimensional stability.

[0117] The effects of the present invention are not limited to the above-mentioned effects. It should be understood that the effects of the present invention include all the effects that can be inferred from the foregoing description of the present invention.

[0118] The invention has been described in detail with reference to exemplary embodiments. However, those skilled in the art will appreciate that changes may be made in these embodiments without departing from the principles and spirit of the invention, the scope of which is defined in the appended claims and their equivalents.

Claims

1. A method for manufacturing a membrane-electrode assembly for a fuel cell, comprising: preparing a first mixture comprising a phosphonic acid precursor material and graphene oxide; preparing a second mixture comprising an active additive and the first mixture; separating the second mixture into a liquid phase and a solid phase; drying the separated solid phase to obtain a solid powder; washing the solid powder to obtain phosphonic acid functionalized graphene oxide; preparing a third mixture comprising phosphonic acid functionalized graphene oxide and a perfluorosulfonic acid ionomer solution; preparing an electrolyte membrane by coating and drying the third mixture; and attaching electrodes to the first and second surfaces of the electrolyte membrane; wherein the electrolyte membrane comprises 0.01 wt % to 10.0 wt % of phosphonic acid functionalized graphene oxide based on the total weight of the electrolyte membrane, wherein the graphene oxide comprises an oxygen-containing functional group selected from a carboxyl group, a hydroxyl group, an epoxy group and a combination thereof, and the phosphonic acid forms a covalent bond with the oxygen of the oxygen-containing functional group, The phosphonic acid precursor material includes triethyl phosphite, and the active additive is used to activate the oxygen groups existing on the surface of graphene oxide.

2. The method according to claim 1, wherein: When preparing the first mixture, the graphene oxide in an amount of 0.1 to 1.0 parts by weight is mixed with 100 parts by weight of the phosphonic acid precursor material.

3. The method according to claim 1, wherein: The active additive includes lithium bromide.

4. The method according to claim 1, wherein: In preparing the second mixture, the active additive is introduced into the first mixture in an amount of 0.2 to 2.0 parts by weight based on 100 parts by weight of the phosphonic acid precursor material.

5. The method according to claim 1, wherein: The solid powder is washed with one or more selected from tetrahydrofuran, dimethylformamide and water.

6. The method according to claim 1, further comprising: attaching an ionomer composite membrane to the first and second surfaces of the electrolyte membrane prior to attaching the electrodes, Each ionomer composite membrane includes a porous reinforced membrane, and the pores in the porous reinforced membrane are impregnated with perfluorosulfonic acid ionomer.

7. A membrane-electrode assembly for a fuel cell obtained by the method for manufacturing a membrane-electrode assembly for a fuel cell according to claim 1, wherein the membrane-electrode assembly comprises: an electrolyte membrane comprising graphene oxide; as well as a pair of electrodes disposed on a first surface and a second surface of the electrolyte membrane, wherein the electrolyte membrane comprises 0.01 wt % to 10.0 wt % of phosphonic acid functionalized graphene oxide based on the total weight of the electrolyte membrane, The graphene oxide comprises an oxygen-containing functional group selected from a carboxyl group, a hydroxyl group, an epoxy group and a combination thereof, and the phosphonic acid forms a covalent bond with oxygen of the oxygen-containing functional group.

8. The membrane-electrode assembly for a fuel cell according to claim 7, wherein: The electrolyte membrane includes a perfluorosulfonic acid ionomer.

9. The membrane-electrode assembly for a fuel cell according to claim 7, wherein: The electrolyte membrane has a water absorption rate of 50% or more.

10. The membrane-electrode assembly for a fuel cell according to claim 7, wherein: The electrolyte membrane has a proton conductivity of 0.04 to 0.40 S / cm.

11. The membrane-electrode assembly for a fuel cell according to claim 7, further comprising: a pair of ionomer composite membranes, each ionomer composite membrane comprising a porous reinforcement membrane, The ionomer composite membrane is disposed between the electrode and the electrolyte membrane so as to be attached to the first surface and the second surface of the electrolyte membrane.

12. The membrane-electrode assembly for a fuel cell according to claim 11, wherein Each ionomer composite membrane also includes a perfluorosulfonic acid ionomer, and The ionomer is impregnated into the pores of the porous reinforced membrane.

13. The membrane-electrode assembly for a fuel cell according to claim 11, wherein: The porous reinforced membrane comprises at least one selected from polytetrafluoroethylene, expanded polytetrafluoroethylene, polyethylene, polypropylene, polyphenylene ether, polybenzimidazole, polyimide, polyvinylidene fluoride and polyvinyl chloride.

14. A fuel cell comprising the membrane-electrode assembly according to claim 7.

Citation Information

Patent Citations

  • Nafion / phosphorylation graphene oxide hybrid membrane and preparation and application thereof

    CN105742677A

  • Amphiphilic aerogel and preparation method thereof

    CN107244667A

  • Method for synthesizing phosphonic acid modified graphene or phosphonate modified graphene

    CN108570072A

  • Phosphate functionalized graphene oxide based bone scaffolds

    WO2018204702A1